2011
DOI: 10.1021/jo2012658
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Dermostatin A

Abstract: The concise total synthesis of dermostatin A is described. Highlights include a two-directional application of the asymmetric acetate aldol method developed in our lab, a novel diastereotopic-group-selective acetal isomerization for terminus differentiation, and a selective cross-metathesis reaction between a terminal olefin and a trienal. A study of the scope and viability of similar cross-metathesis reactions is also described. The synthesis is convergent and utilizes fragments of roughly equal complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 81 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Schreiber was a pioneer of the two-directional chain extension/ terminus differentiation strategy [132] and his group has employed the approach in magnificent syntheses of a range of unsymmetrical targets, including hikizimycin [133] and mycoticins A and B. [134] This strategy remains popular, with recent examples including those from the laboratories of Zhang, [135] Metz, [136] Molinski, [137] Blakemore, [138] Nelson, [139] and Vogel. [140] Stockman and coworkers have reported the application of the two-directional approach in both target and diversity oriented synthesis.…”
Section: Independent Reactionsmentioning
confidence: 99%
“…Schreiber was a pioneer of the two-directional chain extension/ terminus differentiation strategy [132] and his group has employed the approach in magnificent syntheses of a range of unsymmetrical targets, including hikizimycin [133] and mycoticins A and B. [134] This strategy remains popular, with recent examples including those from the laboratories of Zhang, [135] Metz, [136] Molinski, [137] Blakemore, [138] Nelson, [139] and Vogel. [140] Stockman and coworkers have reported the application of the two-directional approach in both target and diversity oriented synthesis.…”
Section: Independent Reactionsmentioning
confidence: 99%
“…[20] The authors found that subjecting 64 to PPTS in toluene at 110 °C allowed a trans-ketalization to give 65 with perfect diastereoselectivity. Although they observed a 9:1 mixture of internal acetal to terminal acetal, they were able to isolate 65a in 82% yield.…”
Section: Diastereotopic Group Selection and Configurational Definimentioning
confidence: 99%
“…The key building block was prepared through hydrogen borrowing catalysis (Scheme 19). [22] Using the simple, cheap, achiral starting material 67 , the authors were able to use an ( S )-Ir-SEGPHOS complex to catalyze a double anti -crotylation with 3-butenyl-2-acetate to give 68 .…”
Section: Diastereotopic Group Selection and Configurational Definimentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Sammakia and coworkers described the total synthesis of the macrolide dermostatin A (133) [57]. In their synthetic approach, the authors coupled the boron enolate of the methyl ketone 130 with the aldehyde 131, which formed the aldol adduct 132 with excellent selectivity toward the 1,5-anti isomer.…”
Section: ) [48]mentioning
confidence: 99%